Evaluation of the Futsal Extracurricular Program: Developing Students’ Life Skills Vocational High School - Farcham Mulloh; Amung Ma'mun; Nurlan Kusmaedi; Bambang Abduljabar; Febrian Andi Hidayat; Raisa Anakotta; Waskito Aji Suryo Putro (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to evaluate the effectiveness of integrating life skills education into futsal extracurricular activities in vocational high schools. The research was conducted in response to the limited application of life skills learning in sports-based programs, particularly in futsal, which is often focused merely on technical performance. Methodology: The study employed a quantitative descriptive approach using the CIPP (Context, Input, Process, Product) model. The participants were 13 students purposively selected from the extracurricular futsal program at Vocational High School Muhammadiyah Kutawinangun. Data were collected using validated questionnaires to measure life skills and performance tests to assess basic futsal skills (dribbling, passing, and shooting). The data were analyzed using paired sample t-tests and N-Gain to determine the effectiveness of the intervention. Main Findings: The results showed a significant improvement in students’ life skills (M = 50.69; t = 8.957; p < 0.001) and a moderate improvement in futsal skills (M = 9.39; t = 3.501; p = 0.004). The integration of structured life skills learning within futsal training proved effective in developing students’ teamwork, communication, and self-management abilities. Novelty/Originality of this study: The novelty of this study lies in its systematic combination of sports pedagogy and life skills education within an extracurricular setting, providing a new model for holistic learning in vocational education. The findings have practical implications for educators and policymakers in designing sports-based learning models that foster students’ personal, social, and professional competencies in alignment with 21st-century education goals.